Distribution of Arbuscular Mycorrhizal (AM) Fungi in Association with some Important Medicinal Plants of Tamil Nadu - Mohan, V.; Bappammal, M.; Malathy, N.; Manokaran, P. (Indian Forester, 2005)
The status of the Arbuscular Mycorrhizal (AM) fungi associated with the roots of ten different medicinal plants viz., Aristolochia bracteata, Centella asiatica, Cichorium intybus, Eclipta prostrata, Hygrophylla auriculata, Indoneesiella echioides, Ocimum sanctum, Oxalis corniculata, Phyla nodiflora and Solanum trilobatum belonging to eight families such as Apiaceae, Aristolochiaceae, Solanaceae, Verbenaceae, Oxalidaceae, Labiatae, Acanthaceae and Asteraceae growing in the State Forest Department's medicinal garden at Aliyar, Tamil Nadu was investigated. The study revealed that all the plant species had AM colonization in the roots and spore population in the rhizosphere soils. But there is a variation in per cent colonization in the roots and soil spore population in different plant species. Among different plants studied, maximum percent root colonization and soil spore population of AM fungi were observed in the plant samples of Ocimum sanctum and Centella asiatica. Low per cent colonization and soil spore population was observed in the plant samples of Cichorium intybus. Among different AM fungi isolated and identified, the most dominant was Glomus which had ten different species found in the rhizosphere of different medicinal plants studied.